Pengaruh Latar Belakang Ekonomi, Pendidikan, dan Motivasi Orang Tua terhadap Prestasi Siswa SDN 02 Sukorejo Kulon - Pusporini, Endang; Arifin, Zainal; Surindra, Bayu (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study was to determine the effect of: 1) Parents' economic status on learning achievement. 2) Parents' educational background on learning achievement. 3) Parents' motivation on learning achievement. 4) Parents' socioeconomic status, education, and motivation on children's learning outcomes. Likert scale-based questionnaires were used to collect data where the sampling technique used was saturated sampling, which was then analysed using the classical assumption test, multiple linear regression, hypothesis testing, and the coefficient of determination on a saturated sample of 43 respondents using quantitative causality method. The results show that all variables have a significant effect on learning achievement, with economic background (sig. 0.000), education (sig. 0.024), and learning motivation (sig. 0.000) each having a significance value <0.05. Simultaneously, these three factors also have a significant effect with a sig. 0,002. This study not only evaluates the impact of each factor separately, but also examines how the combination of the three affects student learning achievement.